Nilai Insaniyah Mediasi Penal - Nur Isti Qomatun Nafi’a; Kuswardani Kuswardani (Program Studi Hukum Universitas Pamulang, 2021)
The settlement of criminal cases with peace called penal mediation is the settlement of cases outside the judicial process. Eleventh United Nation Congress on Crime Prevention and Criminal Justice in Bangkok 18-25 April 2005 in Resolution No. A/conf.2033/18 acknowledges that penal mediation is a reference for resolving all criminal cases, without being able to impose imprisonment, but it is necessary to pay attention to the rights of victims and perpetrators, to realize restorative justice. This study will discuss the regulation of penal mediation as an alternative to criminal case settlement in Positive law, as well as the human values contained in Decision No.19/Pid.Sus/2019PN.Sim. and Decision No.1/Pid.C/2021/PN.Rgt. This research is a descriptive research with a juridical-normative approach. The results of this study indicate that penal mediation arrangements can be found in Indonesian positive law, but these regulations are under the law. The human value of the judge's decision is reflected when the victim and perpetrator have a balanced position, there is no win-win position, and the disturbed balance of society can be restored as before.